The influence of subjective norm on intention to use of learning management system among Malaysian higher education students - Baleghi-Zadeh, Sousan; Mohd Ayub, Ahmad Fauzi; Mahmud, Rosnaini; Mohd Daud, Shaffe (AIP Publishing LLC, 2014)
In recent years, the use of learning management system by universities has been increasingly growing. However, the results of several studies have revealed that students do not fully use the information systems. The present study proposes a model which investigates the influence of three constructs of perceived ease of use, perceived usefulness, and subjective norm on behavior intention to use of learning management system. The sample size was 216 Malaysian undergraduate students. The results of the study revealed that the proposed model accounts for 31.1 % variance of behavior intention to use.